2020
DOI: 10.1186/s12889-020-09695-1
|View full text |Cite
|
Sign up to set email alerts
|

Chinese public’s knowledge, perceived severity, and perceived controllability of COVID-19 and their associations with emotional and behavioural reactions, social participation, and precautionary behaviour: a national survey

Abstract: Background The outbreak of the coronavirus disease-19 (COVID-19) has caused enormous stress among the public in China. Intellectual input from various aspects is needed to fight against COVID-19, including understanding of the public’s emotion and behaviour and their antecedents from the psychological perspectives. Drawing upon the cognitive appraisal theory, this study examined three cognitive appraisals (i.e., perceived severity, perceived controllability, and knowledge of COVID-19) and their associations wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
165
2
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(194 citation statements)
references
References 36 publications
17
165
2
10
Order By: Relevance
“…In particular, there is a lack of platforms and channels to support medical students in providing volunteer services. Under the background of public health emergencies, health service workers faced overload work, the challenge of health resources serious scarce, more social participation and support is required ( Li et al, 2020 ), this study focused on the medical students to participate in volunteer service real attitude, motivation and incentive mechanism research, the academic research helps to improve college students volunteer service incentive mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there is a lack of platforms and channels to support medical students in providing volunteer services. Under the background of public health emergencies, health service workers faced overload work, the challenge of health resources serious scarce, more social participation and support is required ( Li et al, 2020 ), this study focused on the medical students to participate in volunteer service real attitude, motivation and incentive mechanism research, the academic research helps to improve college students volunteer service incentive mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The only certainty is the uncertainty.” Previous research emphasized the negative impact of uncertainty, insecurity, and instability on mental health and psychological well-being ( Ornell et al, 2020 ; Torales et al, 2020 ). They underlined that uncertainty and the low predictability of COVID-19 personal, social, and financial consequences, are affecting people’s mental health, due to their difficulty to react successfully and satisfactorily to the situation, especially with regard to anxiety management ( Jeong et al, 2016 ; Cao et al, 2020 ; Li et al, 2020a , b ; Li S. et al, 2020 ; Wang et al, 2020 ). In a pandemic, fear and insecurity increase anxiety levels in healthy individuals and intensify the symptoms of those pre-existing psychiatric disorders ( Shigemura et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies among the Chinese general population have found that symptoms of anxiety have shown a higher increase due to COVID-19 ( Li et al, 2020a , b ; Wang et al, 2020 ). In one study, about a third of the interviewees reported moderate to severe anxiety, while they reported lower depressive and stress scores ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Этот «эффект большинства», получивший в социальной психологии название дескриптивных норм, когда поведение человека определяется представлением о наиболее типичном поведении других членов социальной группы, Полученные данные хорошо согласуются с результатами других исследователей. Так, оказалось, что убеждение в контролируемости угрозы COVID-19 позитивно влияет на психологическое благополучие и повышает готовность следовать правилам предосторожности [Li et al, 2020]; наибольший отклик получают сообщения с призывом оставаться дома из сострадания к людям, уязвимым в отношении COVID-19 [Blagov, 2020]; сострадание к заболевшим в сочетании с тревогой по поводу эпидемии повышает готовность к вакцинации и использованию дезинфицирующих средств [King, Kamble, DeLongis, 2016], а также мотивацию к социальному дистанцированию в условиях пандемии COVID-19 [Pfattheicher et al, 2020].…”
Section: социально-психологические предпосылки институционального довunclassified